PENGARUH ISU PEMAKAIAN FORMALIN TERHADAP PERSEPSI MASYARAKAT DI PURWOKERTO - Zulaikha, Siti; Novandari, Weni; Suliyanto, Suliyanto (Performance, 2007)
The aim of this research to analyze the influence of using formalin to consumer’s tofu perception in Purwokerto. Primary data was collected using questionnaire. Sample of this research consist of 110 tofu consumer’s in Purwokerto. The analysis’ tool that used is non parametric statistic (Binomial test, Cochran test and Mc-Nemar test) with the help of SPSS Version 11 th.00 Software. The result of this research shown that tofu is associated with formalin by consumer. Variables that considered by consumers in buying tofu before break out of formalin issue are tenderness, color, smell, durability, esthetic performance, producers, seller and price. But after the break out of formalin issue, the variables that considered by consumers in buying tofu are tenderness, color, smell, durability and producers. Formalin issue make consumer worry to eat tofu, but level of switching tofu consumer’s to other product is low.